Advances in corneal graft rejection. Issue 4 (July 2021) - Yin, Jia
Abstract : Purpose of review: Immune rejection after corneal transplantation is a major risk for graft failure. We aim to summarize recent advances in the understanding and management of graft rejection. Recent findings: Immune rejection remains the leading cause of graft failure in penetrating keratoplasty (PKP). While ABO blood type and sex match between donor and recipient may reduce rejection, human leucocyte antigens class II matching in a randomized study did not reduce the risk of rejection in high-risk PKP. Compared with PKP, deep anterior lamellar keratoplasty, descemet stripping automated endothelial keratoplasty, and descemet membrane endothelial keratoplasty have lower immune rejection rates of 1.7–13%, 5–11.4%, and 1.7–2.8%, respectively, based on long-term (5 years and more) studies. Whether immune rejection is a major risk factor for graft failure in these lamellar keratoplasties is unclear. While there have not been major advances in the systemic management of graft rejection, topical nonsteroid agents such as tacrolimus and anti-vascular endothelial growth factor have shown promise in high-risk cases. Summary: Immune rejection remains the leading cause of graft failure in PKP. Lamellar keratoplasties have significantly lower rejection rates compared with PKP. The significance of rejection in the failure of lamellar grafts warrants further investigation.